2014
DOI: 10.7150/ijms.8206
|View full text |Cite
|
Sign up to set email alerts
|

Association Study of ARL15 and CDH13 with T2DM in a Han Chinese Population

Abstract: Several studies indicate that plasma adiponectin levels are associated with the risk of type 2 diabetes mellitus (T2DM) or T2DM risk factors in diverse populations. In addition to the adiponectin gene, several other genes have been postulated to influence plasma adiponectin levels. In this study, we investigated two single nucleotide polymorphisms (SNPs), rs4311394 and rs4783244, located intronically in the ADP-ribosylation factor-like protein 15 (ARL15) and the T-cadherin (CDH13) genes, respectively. These SN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 43 publications
0
10
1
Order By: Relevance
“…This study also showed that in Yanbian Korean Chinese population, a subject with genotype GG for SNP rs26770 in ARL15 would manifest higher risk for T2D development with conspicuous traits of recessive inheritance. But we did not find the polymorphisms of alleles on rs4311394 are related to T2D development as do in Richards et al's research on Europeans and Li et al's research on Yunnan Han Chinese population [5,6]. The difference may be due to ethnic specificity.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…This study also showed that in Yanbian Korean Chinese population, a subject with genotype GG for SNP rs26770 in ARL15 would manifest higher risk for T2D development with conspicuous traits of recessive inheritance. But we did not find the polymorphisms of alleles on rs4311394 are related to T2D development as do in Richards et al's research on Europeans and Li et al's research on Yunnan Han Chinese population [5,6]. The difference may be due to ethnic specificity.…”
Section: Discussioncontrasting
confidence: 79%
“…Even though its pathogenesis is still not completely understood, but the insulin resistance and its relative scarcity are surely primary causes for hyperglycemia. In 2009, a study with genome-wide association studies (GWAS) on the single nucleotide polymorphisms (SNPs) which are located in the gene of ADPribosylation factor-like 15 (ARL15) by Richards et al showed that the all ele rs4311394G is highly related to hypoadiponectinemia and T2D with coronary artery disease (CAD) on Europeans [5] and in 2014, Li et al found the same allele is associated with T2D development [6]. These previous studies manifest polymorphisms of ARL15 may play important roles in T2D development and its complications.…”
Section: Introductionmentioning
confidence: 98%
“…However, given the high frequencies of the G allele at rs4783244 (70.7%) and the C allele at rs12922394 (73.4%) related to the elevated levels of adiponectin in control subjects, the effects of the genotypes on the susceptibility of COPD were limited. The frequency of the T allele at rs4783244 was 29.3% in our control subjects, which appears to be lower than the 36% in non-diabetic Han Chinese subjects [30] . This might be attributable to the differences between the two studies in subjects' age, gender, and smoking history.…”
Section: Discussionmentioning
confidence: 87%
“…This might be attributable to the differences between the two studies in subjects' age, gender, and smoking history. Compared to the non-diabetic subjects in Li's study [30] , our control subjects are older (65±8 years vs 50±11 years), more likely to be male (88% vs 63%), and heavier smokers. Indeed, T allele frequency is approximately 29% in Han Chinese in HapMap project data, which is comparable to our results.…”
Section: Discussionmentioning
confidence: 99%
“…During our systematic study of Arl group small G proteins, we focused on Arl15 due to its genetic implication in human diseases (Corre et al, 2018;Danila et al, 2013;Glessner et al, 2010;Li et al, 2014;Negi et al, 2013;Replication et al, 2014;Richards et al, 2009;Ried et al, 2016;Sun et al, 2015;Willer et al, 2013).…”
Section: Arl15-gtp Can Directly Interact With Smad4mentioning
confidence: 99%